pinocchio  2.6.10
A fast and flexible implementation of Rigid Body Dynamics algorithms and their analytical derivatives
CheatSheet: SE(3) operations
\( \newcommand{\BIN}{\begin{bmatrix}} \newcommand{\BOUT}{\end{bmatrix}} \newcommand{\calR}{\mathcal{R}} \newcommand{\calE}{\mathcal{E}} \newcommand{\repr}{\cong} \newcommand{\dpartial}[2]{\frac{\partial{#1}}{\partial{#2}}} \newcommand{\ddpartial}[2]{\frac{\partial^2{#1}}{\partial{#2}^2}} \newcommand{\aRb}{\ {}^{A}R_B} \newcommand{\aMb}{\ {}^{A}M_B} \newcommand{\amb}{\ {}^{A}m_B} \newcommand{\apb}{{\ {}^{A}{AB}{}}} \newcommand{\aXb}{\ {}^{A}X_B} \newcommand{\bRa}{\ {}^{B}R_A} \newcommand{\bMa}{\ {}^{B}M_A} \newcommand{\bma}{\ {}^{B}m_A} \newcommand{\bpa}{\ {}^{B}{BA}{}} \newcommand{\bXa}{\ {}^{B}X_A} \newcommand{\ap}{\ {}^{A}p} \newcommand{\bp}{\ {}^{B}p} \newcommand{\afs}{\ {}^{A}\phi} \newcommand{\bfs}{\ {}^{B}\phi} \newcommand{\af}{\ {}^{A}f} \renewcommand{\bf}{\ {}^{B}f} \newcommand{\an}{\ {}^{A}\tau} \newcommand{\bn}{\ {}^{B}\tau} \newcommand{\avs}{\ {}^{A}\nu} \newcommand{\bvs}{\ {}^{B}\nu} \newcommand{\w}{\omega} \newcommand{\av}{\ {}^{A}v} \newcommand{\bv}{\ {}^{B}v} \newcommand{\aw}{\ {}^{A}\w} \newcommand{\bw}{\ {}^{B}\w} \newcommand{\aI}{\ {}^{A}I} \newcommand{\bI}{\ {}^{B}I} \newcommand{\cI}{\ {}^{C}I} \newcommand{\aY}{\ {}^{A}Y} \newcommand{\bY}{\ {}^{B}Y} \newcommand{\cY}{\ {}^{c}Y} \newcommand{\aXc}{\ {}^{A}X_C} \newcommand{\aMc}{\ {}^{A}M_C} \newcommand{\aRc}{\ {}^{A}R_C} \newcommand{\apc}{\ {}^{A}{AC}{}} \newcommand{\bXc}{\ {}^{B}X_C} \newcommand{\bRc}{\ {}^{B}R_C} \newcommand{\bMc}{\ {}^{B}M_C} \newcommand{\bpc}{\ {}^{B}{BC}{}} \)

Rigid transformation

\(m : p \in \calE(3) \rightarrow m(p) \in E(3)\)
Transformation from B to A:
\(\amb : \bp \in \calR^3 \repr \calE(3) \ \rightarrow\ \ap = \amb(\bp) = \aMb\ \bp\)
\( \ap = \aRb \bp + \apb\)
\(\aMb = \BIN \aRb & \apb \\ 0 & 1 \BOUT \)
Transformation from A to B:
\(\bp = \aRb^T \ap + \bpa, \quad\textrm{with }\bpa = - \aRb^T \apb\)
\(\bMa = \BIN \aRb^T & - \aRb^T \apb \\ 0 & 1 \BOUT \)
For Featherstone, \(E = \bRa =\aRb^T\) and \(r = \apb\). Then:
\(\bMa = \BIN \bRa & -\bRa \apb \\ 0 & 1 \BOUT = \BIN E & -E r \\ 0 & 1 \BOUT \)
\(\aMb = \BIN \bRa^T & \apb \\ 0 & 1 \BOUT = \BIN E^T & r \\ 0 & 1 \BOUT \)

Composition

\( \aMb \bMc = \BIN \aRb \bRc & \apb + \aRb \bpc \\ 0 & 1 \BOUT \)
\( \aMb^{-1} \aMc = \BIN \aRb^T \aRc & \aRb^T (\apc - \apb) \\ 0 & 1 \BOUT \)

Motion Application

\(\avs = \BIN \av \\ \aw \BOUT\)
\(\bvs = \bXa\avs\)
\( \aXb = \BIN \aRb & \apb_\times \aRb \\ 0 & \aRb \BOUT \)
\( \aXb^{-1} = \bXa = \BIN \aRb^T & -\aRb^T \apb_\times \\ 0 & \aRb^T \BOUT \)
For Featherstone, \(E = \bRa =\aRb^T\) and \(r = \apb\). Then:
\( \bXa = \BIN \bRa & - \bRa \apb_\times \\ 0 & \bRa \BOUT = \BIN E & -E r_\times \\ 0 & E \BOUT\)
\( \aXb = \BIN \bRa^T & \apb_\times \bRa^T \\ 0 & \bRa^T \BOUT = \BIN E^T & r_\times E^T \\ 0 & E^T \BOUT\)

Force Application

\(\afs = \BIN \af \\ \an \BOUT\)
\(\bfs = \bXa^* \afs\)
For any \(\phi,\nu\), \(\phi\dot\nu = \afs^T \avs = \bfs^T \bvs\) and then:
\(\aXb^* = \aXb^{-T} = \BIN \aRb & 0 \\ \apb_\times \aRb & \aRb \BOUT\)
(because \(\apb_\times^T = - \apb_\times\)).
\(\aXb^{-*} = \bXa^* = \BIN \aRb^T & 0 \\ -\aRb^T \apb_\times & \aRb^T \BOUT\)
For Featherstone, \(E = \bRa =\aRb^T\) and \(r = \apb\). Then:
\(\bXa^* = \BIN \bRa & 0 \\ -\bRa \apb_\times & \bRa \BOUT = \BIN E & 0 \\ - E r_\times & E \BOUT \)
\(\aXb^* = \BIN \bRa^T & 0 \\ \apb_\times \bRa^T & \bRa^T \BOUT = \BIN E^T & 0 \\ r_\times E^T & E^T \BOUT \)

Inertia

Inertia application

\(\aY: \avs \rightarrow \afs = \aY \avs\)
Coordinate transform:
\(\bY = \bXa^{*} \aY \bXa^{-1}\)
since:
\(\bfs = \bXa^* \bfs = \bXa^* \aI \aXb \bvs\)
Cannonical form. The inertia about the center of mass \(c\) is:
\(\cY = \BIN m & 0 \\ 0 & \cI \BOUT\)
Expressed in any non-centered coordinate system \(A\): \(\aY = \aXc^* \cI \aXc^{-1} = \BIN m & m\ ^AAC_\times^T \\ m\ ^AAC_\times & \aI + m \apc_\times \apc\times^T \BOUT \)
Changing the coordinates system from \(B\) to \(A\):
\(\aY = \aXb^* \bXc^* \cI \bXc^{-1} \aXb^{-1} \) \( = \BIN m & m [\apb + \aRb \bpc]_\times^T \\ m [\apb + \aRb \bpc]_\times & \aRb \bI \aRb^T - m [\apb + \aRb \bpc]_\times^2 \BOUT\)
Representing the spatial inertia in \(B\) by the triplet \((m,\bpc,\bI)\), the expression in \(A\) is:
\( \amb: \bY = (m,\bpc,\bI) \rightarrow \aY = (m,\apb+\aRb \bpc,\aRb \bI \aRb^T)\)
Similarly, the inverse action is:
\( \amb^{-1}: \aY \rightarrow \bY = (m,\aRb^T(^AAC-\apb),\aRb^T\aI \aRb) \)
Motion-to-force map:
\( Y \nu = \BIN m & mc_\times^T \\ mc_\times & I+mc_\times c_\times^T \BOUT \BIN v \\ \omega \BOUT = \BIN m v - mc \times \omega \\ mc \times v + I \omega - mc \times ( c\times \omega) \BOUT\)
Nota: the square of the cross product is: \(\BIN x\\y\\z\BOUT_ \times^2 = \BIN 0&-z&y \\ z&0&-x \\ -y&x&0 \BOUT^2 = \BIN -y^2-z^2&xy&xz \\ xy&-x^2-z^2&yz \\ xz&yz&-x^2-y^2 \BOUT\) There is no computational interest in using it.

Inertia addition

\( Y_p = \BIN m_p & m_p p_\times^T \\ m_p p_\times & I_p + m_p p_\times p_\times^T \BOUT\)
\( Y_q = \BIN m_q & m_q q_\times^T \\ m_q q_\times & I_q + m_q q_\times q_\times^T \BOUT\)

Cross products

Motion-motion product:
\(\nu_1 \times \nu_2 = \BIN v_1\\\omega_1\BOUT \times \BIN v_2\\\omega_2\BOUT = \BIN v_1 \times \omega_2 + \omega_1 \times v_2 \\ \omega_1 \times \omega_2 \BOUT \)
Motion-force product:
\(\nu \times \phi = \BIN v\\\omega\BOUT \times \BIN f\\ \tau \BOUT = \BIN \omega \times f \\ \omega \times \tau + v \times f \BOUT \)
A special form of the motion-force product is often used:
\(\begin{align*}\nu \times (Y \nu) &= \nu \times \BIN mv - mc\times \omega \\ mc\times v + I \omega - mc\times(c\times \omega) \BOUT \\&= \BIN m \omega\times v - \omega\times(mc\times \omega) \\ \omega \times ( mc \times v) + \omega \times (I\omega) -\omega \times(c \times( mc\times \omega)) -v\times(mc \times \omega)\BOUT\end{align*}\)
Setting \(\beta=mc \times \omega\), this product can be written:
\(\nu \times (Y \nu) = \BIN \omega \times (m v - \beta) \\ \omega \times( c \times (mv-\beta)+I\omega) - v \times \beta \BOUT\)
This last form cost five \(\times\), four \(+\) and one \(3\times3\) matrix-vector multiplication.

Joint

We denote by \(1\) the coordinate system attached to the parent (predecessor) body at the joint input, ad by \(2\) the coordinate system attached to the (child) successor body at the joint output. We neglect the possible time variation of the joint model (ie the bias velocity \(\sigma = \nu(q,0)\) is null).
The joint geometry is expressed by the rigid transformation from the input to the ouput, parametrized by the joint coordinate system \(q \in \mathcal{Q}\):
\( ^2m_1 \repr \ ^2M_1(q)\)
The joint velocity (i.e. the velocity of the child wrt. the parent in the child coordinate system) is:
\(^2\nu_{12} = \nu_J(q,v_q) = \ ^2S(q) v_q \)
where \(^2S\) is the joint Jacobian (or constraint matrix) that define the motion subspace allowed by the joint, and \(v_q\) is the joint coordinate velocity (i.e. an element of the Lie algebra associated with the joint coordinate manifold), which would be \(v_q=\dot q\) when \(\dot q\) exists.
The joint acceleration is:
\(^2\alpha_{12} = S \dot v_q + c_J + \ ^2\nu_{1} \times \ ^2\nu_{12}\)
where \(c_J = \sum_{i=1}^{n_q} \dpartial{S}{q_i} \dot q_i\) (null in the usual cases) and \(^2\nu_{1}\) is the velocity of the parent body with respect to an absolute (Galilean) coordinate system
NB: The abosulte velocity \(\nu_{1}\) is also the relative velocity wrt. the Galilean coordinate system \(\Omega\). The exhaustive notation should be \(\nu_{\Omega1}\) but \(\nu_1\) is prefered for simplicity.
The joint calculations take as input the joint position \(q\) and velocity \(v_q\) and should output \(^2M_1\), \(^2\nu_{12}\) and \(^2c\) (this last vector being often a trivial \(0_6\) vector). In addition, the joint model should store the position of the joint input in the central coordinate system of the previous joint \(^0m_1\) which is a constant value.
The joint integrator computes the exponential map associated with the joint manifold. The function inputs are the initial position \(q_0\), the velocity \(v_q\) and the length of the integration interval \(t\). It computes \(q_t\) as:
\( q_t = q_0 + \int_0^t v_q dt\)
For the simple vectorial case where \(v_q=\dot q\), we have \(q_t=q_0 + t v_q\). Written in the more general case of a Lie groupe, we have \(q_t = q_0 exp(t v_q)\) where \(exp\) denotes the exponential map (i.e. integration of a constant vector field from the Lie algebra into the Lie group). This integration only consider first order explicit Euler. More general integrators (e.g. Runge-Kutta in Lie groupes) remains to be written. Adequate references are welcome.

RNEA

Initialization

\(^0\nu_0 = 0 ; \ ^0\alpha_0 = -g\)
In the following, the coordinate system \(i\) is attached to the output of the joint (child body), while \(lambda(i)\) is the central coordinate system attached to the parent joint. The coordinated system associated with the joint input is denoted by \(i_0\). The constant rigid transformation from \(\lambda(i)\) to the joint input is then \(^{\lambda(i)}M_{i_0}\).

Forward loop

For each joint \(i\), update the joint calculation \(\mathbf j_i\).calc( \(q,v_q\)). This compute \(\mathbf{j}.M = \ ^{\lambda(i)}M_{i_0}(q)\), \(\mathbf{j}.\nu = \ ^i\nu_{{\lambda(i)}i}(q,v_q)\), \(\mathbf{j}.S = \ ^iS(q)\) and \(\mathbf{j}.c = \sum_{k=1}^{n_q} \dpartial{^iS}{q_k} \dot q_k\). Attached to the joint is also its placement in body \(\lambda(i)\) denoted by \(\mathbf{j}.M_0 =\ ^{\lambda(i)}M_{i_0}\). Then:
\(^{\lambda(i)}M_i = \mathbf{j}.M_0 \ \mathbf{j}.M \)
\(^0M_i = \ ^0M_{\lambda(i)} \ ^{\lambda(i)}M_i\)
\(^i\nu_{i}= \ ^{\lambda(i)}X_i^{-1} \ ^{\lambda(i)}\nu_{{\lambda(i)}} + \mathbf{j}.\nu\)
\(^i\alpha_{i}= \ ^{\lambda(i)}X_i^{-1} \ ^{\lambda(i)}\alpha_{{\lambda(i)}} + \mathbf{j}.S \dot v_q + \mathbf{j}.c + \ ^i\nu_{i} \times \mathbf{j}.\nu\)
\(^i\phi_i= \ ^iY_i \ ^i\alpha_i + \ ^i\nu_i \times \ ^iY_i \ ^i\nu_i - \ ^0X_i^{-*}\ ^0\phi_i^{ext}\)

Backward loop

For each joint \(i\) from leaf to root, do:
\(\tau_i = \mathbf{j}.S^T \ ^i\phi_i\)
\(^{\lambda(i)}\phi_{\lambda(i)} \ +\!\!= \ ^{\lambda(i)}X_i^{*} \ ^i\phi_i\)

Nota

It is more efficient to apply \(X^{-1}\) than \(X\). Similarly, it is more efficient to apply \(X^{-*}\) than \(X^*\). Therefore, it is better to store the transformations \(^{\lambda(i)}m_i\) and \(^0m_i\) than \(^im_{\lambda(i)}\) and \(^im_0\).